The Interplay of Psychological Resilience and Job Satisfaction Among Nurses: A Cross‐Sectional Study - Tuğba Uluocak Köse; Ayşe Sevim Ünal; Aydın Avci (International Nursing Review, 2026)
ABSTRACT Aim This study aimed to examine the association between job satisfaction and psychological resilience among nurses and to explore differences in these scores according to selected demographic, occupational, and lifestyle‐related characteristics. Background Job satisfaction and psychological resilience are important work‐related and psychological constructs in nursing. Examining their association may provide insight into nurses’ occupational experiences and inform future workforce‐support strategies. Methods A descriptive, cross‐sectional, and correlational design was used. Data were collected through an online self‐administered questionnaire from 427 nurses working in public, private, and university hospitals in Ankara, Türkiye. The Job Satisfaction Scale and Connor–Davidson Resilience Scale–Short Form were administered. Data were analyzed using descriptive statistics, Pearson correlation analysis, independent‐samples t tests, and one‐way analysis of variance followed by Tukey HSD post‐hoc tests when appropriate. Findings Job satisfaction was positively correlated with psychological resilience ( r = .418, p